The Fire Dragon. Benavente’s Indian Comedy - Enrique Gallud Jardiel (Universitat Autònoma de Barcelona, 2014)
El dragón de fuego is a play by Jacinto Benavente, winner of the Nobel Prize for Literature in 1922, which describes the situation in India during the British Raj. The action takes place in Nirvan, an imaginary country which symbolises India. In an allegorical language the play presents a historical reality: that of the so-called “Sepoy Mutiny”, an armed uprising against colonial rule, which ended in great failure. The article compares the plot of the play with historical events and studies the peculiar position of the author regarding British colonialism, as Benavente, unlike most Spanish intellectuals of the early twentieth century, sided with the Indians who were claiming their independence.